Inclusão de dipeptídeo de metionina na dieta de frangos de corte submetidos ao estresse térmico agudo - Euzébio, Tainara Ciuffi (2018)
There were investigate the methionine supplementation in the dipeptide form and the effect of acute heat stress on the performance and expression of genes PepT1, TNF-? and y+LAT1 in jejunum of broilers chickens. Thus, 90 male broiler chickens, 45 days old, were allocated into 3 groups according to methionine supplementation: without methionine supplementation, DL-Methionine supplementation at the recommended level and methionine supplementation in the form of dipeptide (DL-MMet), each treatment consisting in 6 replicates. The animals were raised up to 44 days in a controlled environment receiving the three diets and at 44 days of age, half of the animals were exposed to heat stress of 38°C for 24 hours. The diet influenced the weight gain, final weight and feed conversion. It was observed that birds supplemented with both forms of methionine had better values for these variables. PepT1 gene expression was not influenced by temperature or diet. For the TNF-? gene there was higher expression for animals consuming the diet without supplementation. The y+LAT gene showed differences in its expression regarding diet and also temperature. Animals supplemented with DL-Methionine showed higher expression of y+LAT gene, as did animals supplemented with DL-MMet. The birds under heat stress presented higher expression of this gene. The results suggest that methionine supplementation influences animal development independently of its form, and that DL-MMet did not alter the expression of the peptide transporter PepT1